The Degradation of congo red color substance in ozonolysis way by the addition of ZnO/ zeolite catalyst and its analysist using HPLC - Zilfa Zilfa; Ria Elvi Susanti (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2021)
The research about the degradation of congo red color substance using the ZnO/ zeolite catalyst and ozonolysis has been conducted. This research includes the production of ZnO/ zeolite catalyst and its usage to degrade the congo red color substance. This research studies about the impact of the variation time of degradation, the effect of ZnO/ zeolite catalyst weight, the effect of time variation towards the degradation by the addition of ZnO/ zeolite catalyst, ZnO and Zeolite. After that, the result after degradation in optimum condition with HPLC (High Performance Liquid Chromatography). The result of the research shows HPLC analysist of Congo red which is degraded in ozonolysis way without the addition of catalyst results in degradation percentage of 77.27%, 88. 41 % in the addition of ZnO catalyst, 90.94% in the addition of Zeolite catalyst,and 93% in the addition of Zno/ zeolite .